DETERMINAN PEMERIKSAAN PAYUDARA SENDIRI SEBULAN SEKALI SECARA TERATUR PADA WANITA USIA SUBUR DI DESA KUBUTAMBAHAN - Desak Ketut Sugiartini; Ari Pertama Watiningsih (Indonesian National Nurses Association (INNA) of Central Java, 2020)
Significant condition occurred in increased rate of breast cancer, based on global statistical data. Awareness of breast cancer prevention methods is very important in reducing morbidity and mortality caused by breast cancer. One of them with breast self-examination (BSE) because it is easy, cheap, privacy, safe and does not require special equipment, but this method is not yet widely applied by most women. The purpose of this study was to determine the determinants of regular breast self-examination once a month by women of childbearing age in the Kubutambahanan Village. The method of research was observational with cross sectional approach. Samples were taken purposively with a large number of samples determined as many as 154 respondents. The independent variables in this study were age, level of education, occupation, family history of breast cancer, distance of health facility coverage, mass media exposure, partner / family support, peer group support, dependent variable in this study was breast self-examination behavior. Data collection using questionnaires with structured interview techniques. The study began in June until September 2019. After the data were collected, univariate, bivariate and multivariate analyzes with logistic regression were performed using software. The results of this study found that the determinant variable of monthly breast self-examination was education level (OR = 5,321.95% CI: -0.324–0.213), mass media access (OR = 3,543.95% CI: -0.213 - 0.124), partner or family support (OR = 7,002.95% CI: -1.342–0.543) and peer age group support (OR = 5,326.95% CI: -3.234–1.342) remain jointly influential for regular monthly breast self examination. Breast self-examination every month is regularly related to factors of education level, mass media access, partner or family support and peer support.